Recurrent Climatic Shocks and Humanitarian Aid : Impacts on Livelihood Outcomes in Malawi - McCarthy, Nancy; Kilic, Talip; Brubaker, Joshua; de la Fuente, Alejandro; Murray, Siobhan (World Bank, Washington, DC, 2021)
Between 2014 and 2016 unprecedented and consecutive climatic shocks ravaged Malawi, one of the poorest countries in the world. The largest ever emergency relief operation in the country’s history ensued. The pathways and extent to which the humanitarian response protected livelihoods remain under researched. This paper uses a unique data set that combines longitudinal household survey data with GIS-based measures of weather shocks and climate conditions and longitudinal administrative data on the World Food Programme’s aid distribution. The paper aims to understand the drivers of humanitarian aid and evaluate the impact of aid and weather shocks on outcomes related to household production and consumption in Malawi. The analysis shows that droughts and floods had consistent negative impacts on a range of welfare outcomes, particularly for households that were subject to sequential shocks. Aid receipt is demonstrated to attenuate such impacts, again particularly for households that experienced the shocks consecutively. Households living in areas subject to a weather shock and with higher World Food Programme aid distribution were more likely to receive food aid, partially explaining the success of aid in mitigating the impacts of shocks. However, there is significant scope for improving the criteria for targeting humanitarian aid beneficiaries.